PETROLEUM, SAFETY AND ENVIROMENT - Chote, F. R.; Kaskantzis, G. N. (Revista de Engenharia Térmica, 2003)
ABSTRACTThe Risks Analysis consists of the systematic exam of an industrial installation (project or existent) to identify the present risks in the system and to form opinion about potentially dangerous occurrences and its possible consequences. There are two types of risks analysis: the qualitative analysis and the quantitative. The qualitative analysis studies all the possible existent risks of the place, and it relates these risks in agreement with the probability of such accidents happen and with the coming consequences of such accidents. The risks that present high probability of happening and that cause great damages to the structure or the people are analyzed, then, in a quantitative way.Two sceneries were specified for the use of quantitative techniques. The studied sceneries are related with the existent risks in the storage of gasoline in drums stored in the Laboratory of Analysis of Fuels of UFPR / ANP. The models associated to the sceneries in studies were obtained of the literature. The studied sceneries were Fire on pools and Unconfined Explosion. For each studied scenery it was possible to evaluate the consequences of material, humans and environmental damages associated to the accidents. The results show that in case of the fire in pool, for a distance of 61.35 m and 42.8 m starting from the center of the flame, burns happen in third degree and first degree, respectively, in people that are not protected and, for the unconfined explosion the results show that for a distance of 15.43 m of the center of the explosion a person has 90% of chance of having tympanum rupture, and for a distance of 9.5 m of the center of the explosion a person has 99% of chance of dying.